Enhanced biofilm solubilization by urea in reverse osmosis membrane systems - Sanawar, H. (2021)
Results indicated that two-stage CO(NH2)2/HCl cleaning was as effective as cleaning with NaOH/HCl in terms of restoring the feed channel pressure drop (>70% pressure drop decrease). One-stage cleaning with urea only was not as effective indicating the importance of the second-stage low pH acid cleaning in weakening the biofilm matrix. All three chemical cleaning protocols were equally effective in reducing the concentration of predominant EPS components protein and carbohydrate (>50% reduction in concentrations). However, urea-based cleaning strategies were more effective in solubilizing protein-like matter and tyrosine-containing proteins. Furthermore, ATP measurements showed that biomass inactivation was up to two-fold greater after treatment with urea-based chemical cleanings compared to the conventional acid/alkali treatment. The applicability of urea as an alternative, economical, eco-friendly and effective chemical cleaning agent for the control of biological fouling was successfully demonstrated.